A furry faux paw - Kara, Jessica (Page Street Publising Co., 2022)
Sometimes Your Best Self Is Your Fursona. Online, MauveCat (a cool, confident, glittering pixie cat) has friends and a whole supportive furry community that appreciates her art. At home, Maeve Stephens has to tiptoe around her hoarder mother's mood and mess. When her life is at its hardest, Maeve can always slip into Mauve, her fursona, and be "the happy one," the bubbliest, friendliest artist in her community--it's even how she made her best friend, Jade. With graduation around the corner, Maeve is ready to put her lonely school days behind her and move on with her life. And while her father hasn't been home since the divorce, he does offer her a dream come true: an all-expenses paid trip to the regional furry convention. Furlympia will have everything Maeve's been missing--friends, art mentors, and other furries! So when her mother forbids her from going, Maeve decides to sneak out on her own. Between hitching a ride with Jade, getting a makeover from a young furry she inspired, and connecting with an art idol who could help Her get into her dream school--the furcon is everything Maeve hoped for and more. A single weekend away shows Maeve how wonderful her life could be, but breaking free of the hoard means abandoning her mother, just like everyone else in their life. And Maeve isn't sure if she can--even if it destroys her, too.